Detection of Diabetic Retinopathy using Local Binary Pattern Variant and K-Nearest Neighbor - Ilmi, Nurul; Aisyah Novitri; Haviz Rizka Pratama (Journal of Informatics and Communication Technology (JICT), 2024)
Detection